Meta-Analysis Study: Could Social Support Reduce Depression and Anxiety during COVID-19 Pandemic? - Chusna, Fat Chiya Nidaul; Purwandari, Eny (Universitas Muhammadiyah Surakarta, 2022)
Purpose: The purpose of this study is to evaluate previous findings regarding the correlation of social support in reducing depression and anxiety during the Covid-19 pandemic. Methodology: The method used is the Prefered reporting Items for Systematic Reviews and Meta-analysis (PRISMA) on 16 primary research journals which were analyzed based on the number of participants (N) of 14.945 and the correlation between variables (r)Results: The results show that the effect size value of social support on depression is -0.40 (95%CI -0.466, -0.287 and p = 0.0) with I2 = 96.2%. While the value of the effect size of social support on anxiety is -0.26 (95%CI -0.33, -0.174 and p = 0.0) with I2 = 94.4%. Based on these findings, social support has a negative correlation to depression and shows a large effect size. Then, social support has negative correlation to anxiety and shows medium effect size. The negative correlation between social support for depression and anxiety shows that when social support increases, depression and anxiety will decrease. Social support can be used to reduce depression and anxiety during the Covid-19 pandemic.